Carbon microspheres and preparation method thereof, positive pole piece, secondary battery and electric device

By using carbon microspheres with high specific surface area as conductive agent in secondary batteries and optimizing the positive electrode sheet formula, the problem of short cycle life of secondary batteries is solved, and the cycle performance and rate performance of the battery are significantly improved.

CN119797322APending Publication Date: 2025-04-11AESC DYNAMICS TECHNOLOGY (HUBEI) LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411999511.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The cycle life of existing secondary batteries is short, mainly due to the poor conductivity of the material, which affects the circulation performance of the battery.

Method used

By introducing carbon microspheres as conductive agents and optimizing the formula of the positive electrode sheet, the resistance of the electrode sheet is improved and the cycle life of the battery is improved. The carbon microspheres are composed of sheet-shaped carbon nanosheets and have a porous three-dimensional structure, which improves the specific surface area and conductivity.

Benefits of technology

The high specific surface area and internal porous structure of the carbon microspheres improve the conductivity and liquid retention ability of the electrode sheet, significantly extend the cycle life of the battery, and improve the rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797322A_ABST
    Figure CN119797322A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a carbon microsphere and a preparation method thereof, a positive pole piece, a secondary battery and an electric device, the carbon microsphere is composed of a sheet-shaped carbon nanosheet, the carbon nanosheet is composed of a carbon nanocage, the carbon nanocage has a porous three-dimensional structure, and the specific surface area of the carbon microsphere is greater than or equal to 1500m < 2 > / g. In the invention, the specific surface area of the carbon microspheres is relatively large, when the carbon microspheres are used as the conductive agent and the dosage of the carbon microspheres is the same as that of a common conductive agent, a conductive network formed in the pole piece is more compact, and the resistance of the positive pole piece is smaller; in addition, the carbon nanocage structure in the carbon microspheres can be filled with electrolyte, more ion transmission channels can be provided in the cycle process, the cycle life of the battery is greatly prolonged, and the electrolyte retention capacity of the pole piece can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to carbon microspheres and preparation methods thereof, positive electrode sheets, secondary batteries and electrical devices. Background Art

[0002] With the rapid development and widespread application of long-range electric vehicles, long-range electronic products, power tools, etc. in the new energy field, improving the cycle life of secondary batteries has become one of the hot demands of the current society. For current secondary batteries, current energy storage batteries (such as lithium iron manganese phosphate batteries) have extremely high requirements for cycle life, and current battery materials (such as lithium iron manganese phosphate batteries or other batteries) have poor conductivity and large internal resistance in power batteries, which affects the cycle performance of the battery and hinders the application of the corresponding battery in the market. Therefore, it is urgent to improve the cycle performance of the battery. Summary of the invention

[0003] The present application improves the resistance of the pole piece and increases the cycle life of the battery by introducing carbon microspheres and optimizing the formula of the pole piece.

[0004] The embodiment of the present application provides a carbon micron ball, which is composed of flaky carbon nanosheets, which are composed of carbon nanocages, and the carbon nanocages have a porous three-dimensional structure, wherein the specific surface area of ​​the carbon micron ball is ≥1500m 2 / g, specifically, the specific surface area of ​​carbon microspheres is: 1500m 2 / g-3000m 2 / g, in this application, the specific surface area of ​​carbon microspheres is relatively large (range ≥1500m 2 / g), which can improve the transmission efficiency of ions and electrons, reduce the resistance of the electrode and improve the conductivity and rate performance of the electrode, thereby improving the cycle performance of the battery.

[0005] In some embodiments, the size of the carbon nanocage is 10 nm-20 nm, the thickness of the carbon nanosheet is ≤100 nm, and the particle size of the carbon microsphere is 2 μm-10 μm.

[0006] The embodiment of the present application also provides a positive electrode sheet, which includes: a positive electrode active material, a binder and a conductive agent, and the conductive agent is the above-mentioned carbon microsphere. Further, based on the total mass of the positive electrode sheet, the mass fraction of the positive electrode active material is 95%-98%, the mass fraction of the binder is 1%-3%, and the mass fraction of the conductive agent is 1%-2%. In some embodiments, the positive electrode active material includes lithium iron manganese phosphate, or nickel cobalt manganese oxide, etc. In some embodiments, the binder includes one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyacrylate, sodium carboxymethyl cellulose, styrene butadiene rubber and polyurethane, and optionally, the binder is vinylidene fluoride (PVDF). In the present application, carbon microspheres are used as conductive agents to improve the conductivity of the positive electrode sheet, such as for lithium iron manganese phosphate positive electrode formula, which can greatly improve the conductivity of the battery positive electrode sheet. The specific formula is as follows: lithium iron manganese phosphate 95-98% + PVDF1%-3% + carbon microspheres 1%-2%. Furthermore, using carbon microspheres to replace conductive agents such as acetylene black, conductive graphite, and carbon nanotubes can significantly improve the performance of the corresponding positive electrode sheets.

[0007] The present application also provides a method for preparing carbon microspheres, the method comprising: heating a metal salt to a first temperature or higher in an inert atmosphere; adding an organic carbon source, keeping the temperature for a first time, and obtaining a carbon-coated metal oxide; removing the metal oxide to obtain a first product; adding the first product to a zinc nitrate solution to obtain a second product; and heating the second product to a second temperature or higher, keeping the temperature for a second time, and obtaining the carbon microspheres, wherein the first temperature is 800°C ± 50°C, and the second temperature is 670°C. In some embodiments, the metal salt includes one or more of magnesium carbonate, zinc carbonate, and iron carbonate, and the organic carbon source includes one or more of benzene, thiophene, pyridine, xylene, and pyrimidine. In some embodiments, the first time is more than 1h, and the second time is more than 2h. In some embodiments, the amount of the organic carbon source added relative to the metal salt is: 40μL / g-100μL / g, and the mass ratio of the zinc nitrate to the first product is 0.5-2:100.

[0008] In addition, embodiments of the present application also provide a secondary battery and a corresponding electrical device.

[0009] The carbon microspheres provided in the present application have a large specific surface area. When they are used as a conductive agent, the conductive network formed in the electrode sheet is denser, making the resistance of the positive electrode sheet smaller. BRIEF DESCRIPTION OF THE DRAWINGS

[0010]

[0013] The corresponding aspects of the embodiments of the present disclosure are best understood from the following detailed description when read in conjunction with the accompanying drawings.

[0011] Figure 1A scanning electron microscope image of the carbon microsphere 100 at 10K magnification is shown.

[0012] Figure 2 An enlarged view of the carbon nanosheet 101 is shown. DETAILED DESCRIPTION

[0013] The applicant found that carbon microspheres have a large specific surface area. When they are used as conductive agents and the same amount as ordinary conductive agents is used, the conductive network formed in the electrode is denser and the resistance of the positive electrode is smaller. In addition, the carbon nanocage structure inside the carbon microspheres can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improving the cycle life of the battery and improving the electrode's ability to retain liquid.

[0014] The embodiments of the present application provide carbon microspheres, which are composed of sheet-like carbon nanosheets. Further, the carbon nanosheets are composed of carbon nanocages, and the carbon nanocages have a porous three-dimensional structure. In the present application, the specific surface area of ​​the carbon microspheres is ≥1500m 2 / g, specifically, the specific surface area of ​​the carbon microspheres is 1500-3000m 2 In this application, the specific surface area of ​​carbon microspheres is relatively large (range ≥1500m 2 / g), when used as a conductive agent, the conductive network formed in the pole piece is more dense and the positive pole piece resistance is smaller when the same amount as the ordinary conductive agent is used. Furthermore, the transmission efficiency of ions and electrons can be improved, the resistance of the pole piece can be reduced, and the conductivity and rate performance of the pole piece can be improved, thereby improving the cycle performance of the battery. In addition, the carbon nanocage structure inside the carbon microsphere can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improve the cycle life of the battery (such as lithium manganese iron phosphate battery), and can improve the liquid retention capacity of the pole piece.

[0015] In some embodiments, the size of the carbon nanocage is 10nm-20nm, and the size is the maximum size of the carbon nanocage in the three-dimensional direction, that is, the size is the length of the carbon nanocage. Further, the thickness of the carbon nanosheet (petal) is ≤100nm. In the present application, when the size of the carbon nanocage is in this range (10nm-20nm), the shape of the carbon nanosheet (such as petal shape) composed thereof is better; optionally, the thickness of the carbon nanosheet (petal) is ≤100nm.

[0016] In the embodiment provided in the present application, the carbon nanosheet has a petal shape formed by the agglomeration of carbon nanocages, that is, the carbon nanosheet can be a petal, and there are petals agglomerated to form a carbon micron flower-shaped carbon micron ball. Optionally, the particle size of the carbon micron ball is 2μm-10μm. In the embodiment provided in the present application, the petal-shaped carbon nanosheets agglomerate to form carbon micron balls, and the particle size of the carbon micron balls is 2μm-10μm, which is used as a conductive agent for the positive electrode of the secondary battery, which can effectively improve the dispersibility of the carbon micron balls in the electrode and form a dense conductive network, and the carbon micron balls composed of petal-shaped carbon nanosheets have a large specific surface area, and there is a certain space / gap between adjacent carbon nanosheets of the carbon micron balls. As a conductive agent, while forming a dense conductive network in the positive electrode, it is also beneficial for the electrolyte to infiltrate the electrode, improve the liquid retention of the electrode, and thus improve the electron and ion conductivity of the positive electrode.

[0017] The embodiment of the present application also provides a positive electrode plate, which includes: a positive electrode active material, a binder and a conductive agent, and the conductive agent is the above-mentioned carbon microspheres. Further, based on the total mass of the positive electrode plate, the mass fraction of the positive electrode active material is 95%-98%, the mass fraction of the binder is 1%-3%, and the mass fraction of the conductive agent is 1%-2%. In some embodiments, the positive electrode active material may include lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium vanadium phosphate, lithium vanadium phosphate, lithium titanate and lithium-rich manganese-based materials. Optionally, the positive electrode active material includes lithium iron manganese phosphate, or nickel cobalt manganese oxide.

[0018] In some embodiments, the binder includes one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyacrylate, sodium carboxymethyl cellulose, styrene-butadiene rubber and polyurethane. Optionally, the binder is vinylidene fluoride (PVDF). In the present application, carbon microspheres are used as conductive agents to improve the conductivity of the positive electrode sheet, such as for lithium iron manganese phosphate positive electrode formula, which can greatly improve the conductivity of the battery positive electrode sheet. The specific formula is as follows: lithium iron manganese phosphate 95-98% + PVDF 1% -3% + carbon microspheres 1% -2%. Furthermore, replacing conductive agents such as acetylene black, conductive graphite and carbon nanotubes with carbon microspheres can significantly improve the performance of the corresponding positive electrode sheet, and applying the corresponding positive electrode slurry made of lithium iron manganese phosphate, PVDF and carbon microspheres to aluminum foil can synthesize a new type of lithium iron manganese phosphate sheet.

[0019] The present application also provides a method for preparing carbon microspheres, the method comprising: heating a metal salt to a first temperature or higher in an inert atmosphere; adding an organic carbon source, keeping the temperature for a first time, and obtaining a carbon-coated metal oxide; removing the metal oxide to obtain a first product; adding the first product to a zinc nitrate solution to obtain a second product; and heating the second product to a second temperature or higher, keeping the temperature for a second time, and obtaining carbon microspheres, wherein the first temperature is 800°C ± 50°C, and the second temperature is 670°C. In some embodiments, the metal salt includes one or more of magnesium carbonate, zinc carbonate, and iron carbonate, and the organic carbon source includes one or more of benzene, thiophene, pyridine, xylene, and pyrimidine. In some embodiments, the first time is more than 1 hour, and the second time is more than 2 hours. In some embodiments, the amount of organic carbon source added relative to the metal salt is: 40 μL / g-100 μL / g, and the mass ratio of zinc nitrate to the first product is 0.5-2:100. When the amount of the organic carbon source or the first product is small, it may not be enough to coat the corresponding metal oxide, thereby reducing the specific surface area of ​​the carbon microspheres formed thereafter. When the amount of the organic carbon source or the first product is too large, it may cause excessive carbon coating, thereby reducing the voids therein, and further reducing the specific surface area of ​​the carbon microspheres formed thereafter. Specifically, the basic magnesium carbonate is heated to a temperature above the first temperature in an inert atmosphere; the organic carbon source benzene is added to the basic magnesium carbonate, and the temperature is kept for a first time to obtain a carbon-coated magnesium oxide material, and the magnesium oxide is removed to obtain a first product; the first product is added to a zinc nitrate solution to obtain a second product; the second product is heated to an etching temperature above 670°C, optionally, an etching temperature above 900°C, further optionally between 670°C-1000°C, and kept at a corresponding temperature for more than 2h, optionally 2h-4h, to obtain the above-mentioned carbon microspheres. In the present application, the basic magnesium carbonate is heated to a temperature above the first temperature in an inert atmosphere to ensure the carbonization of the organic carbon source thereafter. When the temperature is above the first temperature, if the temperature is too high (such as above 1000) / too low (such as below 750°C), the degree of graphitization (or conductivity) of the organic carbon source will be reduced, and too low a temperature will also affect the coating effect of the organic carbon source. In the present application, the reaction involved in magnesium carbonate is: MgCO3→MgO+CO2↑. In some embodiments, the first insulation time is more than 1 hour, which can ensure the full carbonization of the organic carbon source. In addition, the reaction involved in zinc nitrate is: 2Zn(NO3)2→2ZnO+4NO2+O2↑. Heating the second product to an etching temperature above 670°C can ensure the corresponding carbon thermal reduction reaction and the evaporation of Zn. Specifically, when the carbonization temperature is ≥670°C, ZnO will undergo carbon thermal reduction to produce a rich pore structure, and the reaction products Zn and CO2 can be directly evaporated at high temperature. The reaction involved is: 2ZnO(s)+C→2Zn(g)+CO2(g)↑, and the higher the activation temperature, the larger the specific surface area.In addition, ZnO also acts as a graphitization catalyst to improve the conductivity of the material.

[0020] In summary, the preparation method of carbon microspheres provided in the present application may include preparing carbon microspheres by carbon thermal reduction after using a metal salt template method such as magnesium carbonate, zinc carbonate, and iron carbonate, that is, after the carbon microsphere embryo is obtained by the template method, a new hydrothermal method is further used for processing to improve the BET (specific surface area) of the carbon microspheres, thereby improving the transmission efficiency of ions and electrons, and improving the conductivity and rate performance of the pole piece. This is because the template method using metal salts is conducive to the plasticity of carbon microspheres and ensures stability. In the thermal reduction method after the template method, ZnO undergoes a carbon thermal reduction reaction to generate a rich pore structure. The reaction product Zn and CO2 can be directly evaporated at high temperature 2ZnO(s)+C=2Zn(g)+CO2(g)(T≥670℃), thereby forming carbon microspheres with a large specific surface area.

[0021] Specifically, the present application provides the following preparation method of carbon microspheres:

[0022] 1. MgO@C (carbon-coated magnesium oxide material) was prepared by in-situ magnesium oxide template method at 800℃±50℃.

[0023] Basic magnesium carbonate (5 g) was placed in a quartz tube in a vertical furnace and heated at 10 °C min -1 The temperature is raised to above the first temperature at a rate of 50 μL min -1 (Alternatively, 10-60 μL min -1 ) is injected with 300 μL (optionally 200 μL-500 μL) of benzene at a feeding rate of 100 μL / min, kept warm for more than 1 hour, and naturally cooled to room temperature in an Ar gas flow to obtain a mesostructured MgO@C. In some embodiments, the temperature is raised to above the first temperature to ensure the subsequent carbonization of the organic carbon source and the corresponding coating performance, but the temperature cannot be too high, such as above 1000°C, which will reduce the conductivity of the carbon microspheres prepared later.

[0024] 2. Use 6 mol L -1 MgO is removed by HCl (any suitable concentration can be used according to actual conditions), washed with ultrapure water for multiple times until neutral, and freeze-dried to obtain the first product.

[0025] 3. Preparation of carbon microspheres by carbothermal reduction

[0026] 100 mg of the first product was added to 50 mL of an ethanol solution containing 0.5 mg-2 mg of Zn(NO3)2·6H2O, and the mixture was stirred under magnetic heating for more than 12 h at a heating temperature of 70°C-100°C to obtain a second product. The second product was placed in a porcelain boat and placed in a horizontal quartz tube. Under an Ar gas flow of 120 sccm, the tube furnace was heated at 8-12°C min -1 The system is heated to above 670°C (optionally 900°C) at a rate of 1000°C, kept at a temperature above 670°C for more than 2h (optionally 2-4h), and then cooled to room temperature to obtain hierarchical structure carbon microspheres.

[0027] The embodiments of the present application also provide a secondary battery and a corresponding power-consuming device, wherein the secondary battery may be a non-aqueous electrolyte lithium battery or a solid-state lithium battery. Taking a non-aqueous electrolyte lithium battery as an example, it includes a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte, wherein the positive electrode sheet is the above-mentioned positive electrode sheet.

[0028] Specifically, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, etc. Among them, the thickness of the positive electrode current collector is, for example, 8μm to 15μm. In the present embodiment, the positive electrode current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm. The positive electrode current collector has two oppositely disposed surfaces along its own thickness direction, and the positive electrode active material layer can be disposed on the surface of any one side thereof, or on both surfaces. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder, wherein the positive electrode active material includes the above-mentioned lithium manganese iron phosphate, or nickel cobalt manganese oxide Li y Ni x Mn y CoyO2, 0.8≤y≤1.2, 0.8≤x≤1, 0.1≤y≤0.2. In some embodiments, the binder includes one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyacrylate, sodium carboxymethyl cellulose, styrene-butadiene rubber and polyurethane. Optionally, the binder is vinylidene fluoride (PVDF). The conductive agent includes carbon microspheres, and other conductive agents are not limited. Those skilled in the art can choose according to actual needs.

[0029] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector is, for example, copper foil. The negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a thickener. The negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the thickener can be selected from conventional materials in the art, and no specific restrictions are made here.

[0030] As an example, the negative electrode material is selected from carbon and / or silicon negative electrode materials, wherein the carbon negative electrode material can be natural graphite, artificial graphite, soft carbon, hard carbon, etc.; the silicon negative electrode material can be elemental silicon, silicon oxide compounds, silicon carbon compounds, etc. The negative electrode conductive agent is selected from one or a combination of two or more of conductive carbon black, nano silver powder, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR) or a combination of multiple compositions mixed in any proportion; the thickener can be sodium carboxymethyl cellulose (CMC-Na).

[0031] The diaphragm is arranged between the positive electrode and the negative electrode to play an isolating role. The diaphragm can be, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film, a polyethylene film or a composite film. The thickness of the diaphragm is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0032] The electrolyte infiltrates the positive electrode sheet and the negative electrode sheet. During the battery charging and discharging process, lithium ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting lithium ions. The electrolyte can be selected from conventional combinations in the art.

[0033] In one embodiment, the electrolyte includes an organic solvent and a lithium salt, wherein the organic solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), etc. The lithium salt may be selected from one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate), LiTFOP (lithium tetrafluorooxalatophosphate), or a combination thereof in any proportion. The molar concentration of the lithium salt in the electrolyte is 0.5 mol / L to 2 mol / L.

[0034] In other embodiments, some film-forming additives and functional additives that can improve battery performance may be added to the electrolyte, such as vinylene carbonate (VC), 1,3-propane sultone (PS), diethylene sulfate (DTD), etc. Those skilled in the art may select according to actual needs.

[0035] The preparation process of lithium-ion secondary batteries is described below:

[0036] (1) Preparation of positive electrode sheet

[0037] After mixing the positive electrode active material, binder and conductive agent in a mass ratio of 95-98:1-3:1-2, add 80-84 parts by mass of NMP (N-methylpyrrolidone), stir and mix thoroughly to obtain positive electrode slurry; coat the positive electrode slurry on the positive electrode collector aluminum foil, dry, roll, cut and other processes to make positive electrode sheets.

[0038] (2) Preparation of negative electrode sheet

[0039] The above-mentioned negative electrode active material, negative electrode conductive agent, negative electrode binder and thickener are mixed in proportion, deionized water is added and stirred evenly under the stirring action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on the negative electrode collector copper foil, dried at room temperature, transferred to an oven for drying, and cold pressed and cut to obtain a negative electrode sheet.

[0040] (3) Preparation of electrolyte

[0041] In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt (LiPF6) is dissolved in an organic solvent and mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.

[0042] (4) Preparation of diaphragm

[0043] A 12 μm thick polypropylene (PP) or polyethylene (PE) porous polymer film is selected.

[0044] (5) Battery assembly:

[0045] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked or wound in sequence to form a bare battery cell; then wrapped with aluminum plastic film, transferred to a vacuum drying oven and dried at 120°C, sealed after injecting electrolyte, and the electrolyte is formed to finally prepare a soft-pack battery (i.e., a lithium-ion secondary battery).

[0046] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.

[0047] The reagents and raw materials used in the present invention are commercially available.

[0048] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0049] Example 1

[0050] Preparation of positive electrode

[0051] (1) Preparation of carbon microspheres

[0052] 1. MgO@C (carbon-coated magnesium oxide material) was prepared by in-situ magnesium oxide template method at 800°C.

[0053] Basic magnesium carbonate (5 g) was placed in a quartz tube in a vertical furnace and heated at 10 °C min -1 The temperature was raised to 800 °C at a rate of 50 μL min -1 300 μL of benzene was injected at a feeding rate of , and the mixture was kept warm for 1 h. The mixture was naturally cooled to room temperature in an Ar gas flow to obtain the mesostructured MgO@C.

[0054] 2. Use 6 mol L -1 HCl was used to remove MgO, and the product was washed with ultrapure water several times until neutral and freeze-dried to obtain the first product.

[0055] 3. Add 100 mg of carbon microspheres to 50 mL of ethanol solution containing 2 mg of Zn(NO3)2·6H2O, and stir under magnetic heating for 12 h at a heating temperature of 70°C to obtain the second product. Place the second product in a porcelain boat and place it in a horizontal quartz tube. Under an Ar gas flow of 120 sccm, heat the tube furnace at 10°C min. -1 The system was heated to 900°C at a rate of 2 hours, and then cooled to room temperature after being kept at 900°C for a second time of 2 hours, and hierarchical carbon microspheres were obtained. The specific surface area of ​​the carbon microspheres was 3000m 2 / g, the size of the carbon nanocage is 18nm, the thickness of the carbon nanosheet is ≤100nm, and the particle size of the carbon microsphere is 8μm.

[0056] Specifically, see Figure 1 , Figure 1 FIG. 1 shows a scanning electron microscope image of carbon microspheres 100 at 10K magnification. Figure 1 As can be seen from the figure, the carbon microsphere 100 is composed of sheet-like carbon nanosheets 101. Figure 2 As shown, Figure 2 shows an enlarged view of the carbon nanosheet 101, from Figure 2 As can be seen from the figure, the carbon nanosheet 101 is composed of carbon nanocages 102, and the carbon nanocages 102 have a porous three-dimensional structure. Figure 2 This is a TEM transmission image. Figure 2 It can be seen that the black edge of the carbon nano cage 102 is the grain boundary, and the gray is the transparent part, and it is gray after TEM transmission. Therefore, it can be seen that the carbon nano cage 102 is a porous three-dimensional structure. In this application, the specific surface area of ​​the carbon microsphere 100 is 3000m 2 In the present application, the carbon microsphere 100 has a large specific surface area (3000m 2 / g), when used as a conductive agent, the conductive network formed in the electrode is more dense, and the positive electrode resistance is smaller. In addition, the carbon nano cage 102 structure inside the carbon microsphere 100 can be filled with electrolyte, which can provide more ion transmission channels during the cycle process, greatly improve the cycle life of the battery (such as lithium manganese iron phosphate battery), and can improve the electrode liquid retention capacity.

[0057] In this embodiment, the size L of the carbon nano cage 102 is 18 nm, and further, the size L is the maximum size of the carbon nano cage 102 in the three-dimensional direction, that is, the size L is the length of the carbon nano cage 102. Further, the thickness H of the carbon nano sheet (petal) 101 is ≤ 100 nm. In the present application, when the size L of the carbon nano cage 102 is in this range (10 nm-20 nm), the shape (such as petal shape) of the carbon nano sheet 101 composed thereof can be better, and combined with the thickness H of the carbon nano sheet (petal) 101 ≤ 100 nm, the specific surface area of ​​the carbon micro ball 100 formed later can be larger, thereby improving the performance of the battery.

[0058] Return to reference Figure 1 ,from Figure 1 As can be seen from the figure, the carbon nanosheet 101 has a petal-like shape (such as Figure 1 In other words, the carbon nanosheets 101 may be petals, and the petals are aggregated to form the carbon micro-flowers of the carbon micro-spheres 100. Figure 1 ,like Figure 1 As shown, the particle size D of the carbon microsphere 101 is 8 μm. In the present application, the petal-shaped carbon nanosheets 101 are aggregated to form the carbon microsphere 100 of the carbon microsphere, and the particle size D of the carbon microsphere 101 is 2 μm-10 μm. In the present application, the carbon microsphere 100 is a carbon microsphere, and when the particle size D of the carbon microsphere 101 is 2 μm-10 μm, the carbon microsphere 101 can be used as a conductive agent with better dispersion, so that the conductive network formed in the formed positive electrode plate is more dense.

[0059] (2) Preparation of positive electrode sheet

[0060] The positive electrode active material lithium manganese iron phosphate, the binder PVDF, and the conductive agent carbon microspheres are mixed in a mass ratio of 98:1:1, and 82 parts by mass of NMP (N-methylpyrrolidone) are added, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is coated on a positive electrode current collector aluminum foil (8 μm aluminum foil), and the positive electrode sheet is made through processes such as drying, rolling, and cutting.

[0061] Example 2

[0062] The preparation method is consistent with that of Example 1, except that in Example 2, after injecting 300 μL of benzene, the temperature is kept for a first time of 2 h, and then the first product is obtained, and then the second product obtained from the first product is heated to 1000° C. and kept for a second time of 3 h at 1000° C. to obtain carbon microspheres, wherein the specific surface area of ​​the carbon microspheres is 3000 m 2 / g, the size of the carbon nanocage is 16nm, and the particle size of the carbon microsphere is 8μm.

[0063] Example 3

[0064] The preparation method is consistent with that in Example 1, except that in Example 3, basic magnesium carbonate (5 g) is placed in a quartz tube in a vertical furnace and heated to 1000° C., 500 μL of benzene is injected, and the first product is obtained by heating the first product to 1100° C., and the second product is obtained by heating the first product to 1100° C., and the second product is obtained by heating the first product at 1100° C. for 2.5 h to obtain carbon microspheres, wherein the specific surface area of ​​the carbon microspheres is 2500 m 2 / g, the size of the carbon nanocage is 15nm, and the particle size of the carbon microsphere is 6μm.

[0065] Example 4

[0066] The preparation method is consistent with that in Example 1, except that in Example 4, basic magnesium carbonate (5 g) is placed in a quartz tube in a vertical furnace and heated to 1000° C., 350 μL of benzene is injected, and the first product is obtained by heating the first product to 800° C., and the second product is obtained by heating the first product to 800° C., and the second product is obtained by heating the first product at 800° C. for 2 h to obtain carbon microspheres, wherein the specific surface area of ​​the carbon microspheres is 2800 m 2 / g, the size of the carbon nanocage is 13nm, and the particle size of the carbon microsphere is 5μm.

[0067] Example 5

[0068] The preparation method is consistent with that in Example 1, except that in Example 5, basic magnesium carbonate (5 g) is placed in a quartz tube in a vertical furnace and heated to 800° C., 200 μL of benzene is injected, and the temperature is kept for a first time of 1 h to obtain a first product, and then a second product obtained from the first product is heated to 670° C. and kept at 670° C. for a second time of 4 h to obtain carbon microspheres, wherein the specific surface area of ​​the carbon microspheres is 1800 m 2 / g, the size of the carbon nanocage is 10nm, and the particle size of the carbon microsphere is 4μm.

[0069] Example 6

[0070] The preparation method is consistent with that of Example 1, except that the metal salt used in Example 6 is basic zinc carbonate (5 g), wherein the specific surface area of ​​the obtained carbon microspheres is 1900 m 2 / g, the size of the carbon nanocage is 15nm, and the particle size of the carbon microsphere is 4μm.

[0071] Example 7

[0072] The preparation method is consistent with that of Example 1, except that the metal salt used in Example 7 is basic iron carbonate (5 g), wherein the specific surface area of ​​the obtained carbon microspheres is 1600 m 2 / g, the size of the carbon nanocage is 12nm, and the particle size of the carbon microsphere is 3μm.

[0073] Example 8

[0074] The preparation method is consistent with that of Example 1, except that in Example 8, the mass ratio of the positive electrode active material lithium manganese iron phosphate, the binder PVDF, and the conductive agent carbon microspheres is 95:3:2.

[0075] Example 9

[0076] The preparation method is consistent with that of Example 1, except that in Example 9, the mass ratio of the positive electrode active material lithium manganese iron phosphate, the binder PVDF, and the conductive agent carbon microspheres is 96:2.5:1.5.

[0077] Example 10

[0078] The preparation method is the same as that of Example 1, except that the positive electrode active material in Example 10 is nickel cobalt manganese oxide LiNi 0.6 Mn 0.2 Co 0.2 O2(NCM622).

[0079] Embodiment 11

[0080] The preparation method is consistent with that of Example 1, except that in Example 11, the conductive agent is carbon microspheres and acetylene black (mass ratio is 1:1), and the mass ratio of the positive electrode active material lithium manganese iron phosphate, the binder PVDF, and the conductive agent (carbon microspheres and acetylene black) is 95:3:2.

[0081] Example 12

[0082] The preparation method is consistent with that of Example 1, except that in Example 12, thiophene and pyridine (300 μL, mass ratio of 1:1) are used as the organic carbon source, wherein the specific surface area of ​​the carbon microspheres is 1550 m 2 / g, the size of the carbon nanocage is 12nm, the thickness of the carbon nanosheet is ≤100nm, and the particle size of the carbon microsphere is 3μm.

[0083] Comparative Example 1

[0084] The preparation method is consistent with that of Example 1, except that the conductive agent of Example 1 is acetylene black.

[0085] Comparative Example 2

[0086] The preparation method is consistent with that of Example 2, except that the conductive agent of Example 2 is acetylene black.

[0087] Comparative Example 3

[0088] The preparation method was the same as that of Example 1, except that in Comparative Example 3, 5 g of basic magnesium carbonate was placed in a quartz tube in a vertical furnace and heated to 700 °C. Then, 300 μL of benzene was injected, and the mixture was kept at this temperature for 1 h to obtain a first product. Subsequently, the second product obtained from the first product was heated to 800 °C and kept at 800 °C for 2 h to obtain carbon microspheres. The specific surface area of the carbon microspheres was 1000 m 2 / g, the size of the carbon nanocages was 8 nm, and the particle size of the carbon microspheres was 4 μm.

[0089] The testing methods for the carbon microspheres in the above Examples 1-12 and Comparative Examples 1-3 were as follows:

[0090] Specific surface area testing method: A specific surface area and porosity analyzer was used. The above carbon microsphere samples were first degassed and activated at 300 °C for 6 h, and then adsorption measurements were carried out at 77 K using the volumetric method with N2 as the adsorbate. The pore structure and specific surface area were measured on a Thermo Fisher Scientific Surfer Gas Adsorption Porosimeter instrument. The specific surface area was calculated by the BET (Brunauer-Emmett-Teller, 0.05 < p / p0 < 0.3) method, and the pore distribution was obtained by processing the adsorption branch isotherm data using the HK model (Horvath-Kawazoe, < 2 nm micropores) and the BJH model (Barrett-Joyner-Halenda, > 2 nm mesopores and macropores).

[0091] Measurement of the particle size of carbon microspheres:

[0092] Method 1: SEM (scanning electron microscope) images at a magnification of 10K. In the SEM images, at least 5 regions, each region being approximately 12 μm by 12 μm in size, were selected; the diameters of the carbon microspheres in these regions were measured, and the average value was taken;

[0093] The thickness of the carbon nanosheets,

[0094] Measurement of the thickness of carbon nanosheets: SEM (scanning electron microscope) images at a magnification of 10K. A region approximately 12 μm by 12 μm in size was selected in the SEM images, and the thickness of the carbon nanosheets (using the nano measure tool) in this region was measured. The thickness data were statistically analyzed, and the first and last data were removed. The thickness data of the middle 85% were taken as the thickness of the carbon nanosheets;

[0095] Size data of the nanocages

[0096] Nanocage size determination: 10K magnification SEM (scanning electron microscope) image, select an area of ​​about 12μm by 12μm in the SEM image, measure the size of each nanocage (nano measure tool), the size of a nanocage is the distance between the two ends farthest apart, count the size data of each nanocage, remove the first and last ends, and take the size (length) data located at 85% of the middle section as the size of the nanocage.

[0097] Furthermore, the positive electrode sheets in the above-mentioned embodiments 1-12 and comparative examples 1-3 can be formed into secondary batteries by the following method.

[0098] Negative electrode sheet: negative electrode active material graphite, conductive agent (SP), binder (PAA and SBR, the mass ratio of the two is 1.3:0.5) and thickener carboxymethyl cellulose (CMC) are mixed in a mass ratio of 97.2:0.5:1.8:0.5 (a total of 100 parts by mass), and 82 parts by mass of deionized water are added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the copper foil; and then after drying, rolling, cutting and other processes, the negative electrode sheet is prepared.

[0099] Electrolyte: The organic solvent in the electrolyte is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the weight ratio of EC, EMC and DEC is 1:1:1. The electrolyte is LiPF6, and the total content of LiPF6 is 12.5% ​​of the total weight of the electrolyte. Diaphragm: A porous membrane of PE with a thickness of 11um is used as the diaphragm (wherein the thickness of the diaphragm is 9μm to 18μm; the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%).

[0100] Finally, the positive electrode sheet, the separator and the negative electrode sheet are sequentially placed into the mold for assembly; after assembly, the electrolyte is injected, and after formation and packaging, a lithium-ion secondary battery (soft pack, 1.2Ah) is obtained.

[0101] The secondary batteries in the above Examples 1-12 and Comparative Examples 1-3 were subjected to cycle performance tests.

[0102] Cycle performance test method: At 25°C, first charge and discharge the activated battery for one cycle at a rate of 0.1C in the operating voltage range of 2.5V (discharge cut-off voltage) to 4.2V (charge cut-off voltage), then connect the activated lithium-ion battery to the Blue Electric charge and discharge tester, and then perform long-term cycling at a rate of 0.3C within the operating voltage range, and record the capacity Cn of each cycle until the ratio of the capacity of the nth cycle to the capacity of the first cycle of the 0.3C test is 90% or 80%, and the capacity retention rate of the n-1th cycle is defined as 90% or 80%, the number of cycles is recorded as n-1, and the test is stopped.

[0103] The test results are shown in Table 1 below.

[0104]

[0105]

[0106]

[0107] Referring to the above-mentioned Example 1 and Comparative Example 1 as well as the above-mentioned Example 2 and Comparative Example 2, it can be seen that by using the carbon microspheres prepared in the present application as conductive agents, the cycle performance of secondary batteries can be significantly improved. This is because the carbon microspheres have a larger specific surface area, and when used in the same amount as traditional conductive agents, the conductive network formed in the positive electrode plate is denser and the plate resistance is smaller. The carbon cage structure inside the carbon microspheres can be filled with electrolyte, which can provide more ion transmission channels during the cycle process. In addition, the plate's ability to retain liquid can be improved, and the battery cycle life and conductivity can be greatly improved.

[0108] Comparing Examples 1-7 with Comparative Example 3, it can be seen that by controlling the corresponding temperature and the amount of organic carbon source, the specific surface area of ​​the carbon microspheres is ≥1500m 2 / g, specifically, at 1500-3000m 2 / g, the size of the carbon nano cage is between 10nm-20nm and the particle size of the carbon microsphere is between 2μm-10μm, the cycle performance of the battery can be significantly improved, while when the specific surface area of ​​the carbon microsphere is small (for example, 1000m 2 In addition, it can be seen from Examples 1, 6-7 that the use of metal salts including magnesium carbonate, zinc carbonate and iron carbonate can form carbon microspheres with a high specific surface area.

[0109] It can be seen from Examples 8-9 that, based on the total mass of the positive electrode sheet, when the mass fraction of the conductive agent is 1%-2%, when used as the conductive agent of the positive electrode sheet, the cycle life of the corresponding battery can be improved.

[0110] It can be seen from Example 10 that the positive active material of the positive electrode plate can include lithium iron manganese phosphate or nickel cobalt manganese oxide. It can be seen from Example 11 that when the conductive agent includes carbon microspheres, other conductive agents (acetylene black) can be added without affecting the cycle life of the battery.

[0111] In addition, it can be seen from Examples 1 and 12 that the organic carbon source for preparing carbon microspheres can include one or more of benzene, thiophene (carbon with S added), pyridine (carbon doped with N), xylene and pyrimidine, and all of them can obtain carbon microspheres with a large specific surface area (≥1500m 2 / g) of carbon microspheres.

[0112] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.

Claims

1. A carbon microsphere, characterized in that: The carbon microspheres are composed of sheet-like carbon nanosheets, which are composed of carbon nanocages, and the carbon nanocages have a porous three-dimensional structure. Wherein, the specific surface area of ​​the carbon microspheres is ≥1500m 2 / g.

2. The carbon microsphere according to claim 1, characterized in that: The specific surface area of ​​the carbon microspheres is 1500 m 2 / g-3000m 2 / g.

3. The carbon microsphere according to claim 1, characterized in that: The size of the carbon nano cage is 10nm-20nm.

4. The carbon microsphere according to claim 1, characterized in that: The thickness of the carbon nanosheet is ≤100 nm.

5. The carbon microsphere according to claim 1, characterized in that: The particle size of the carbon microspheres is 2 μm-10 μm.

6. A positive electrode sheet, characterized in that: include: A positive electrode active material, a binder and a conductive agent, wherein the conductive agent comprises the carbon microspheres according to any one of claims 1 to 5.

7. The positive electrode sheet according to claim 6, characterized in that: Based on the total mass of the positive electrode plate, the mass fraction of the positive electrode active material is 95%-98%, the mass fraction of the binder is 1%-3%, and the mass fraction of the conductive agent is 1%-2%.

8. A method for preparing carbon microspheres according to any one of claims 1 to 5, characterized in that: include: heating the metal salt to above a first temperature in an inert atmosphere; adding an organic carbon source and keeping the temperature for a first time to obtain a carbon-coated metal oxide; removing the metal oxide to obtain a first product; adding the first product to a solution of zinc nitrate to obtain a second product; as well as The second product is heated to a temperature above the second temperature and kept warm for a second time to obtain the carbon microspheres. Wherein, the first temperature is 800°C±50°C, and the second temperature is 670°C.

9. The method according to claim 8, characterized in that The metal salt comprises one or more of magnesium carbonate, zinc carbonate and iron carbonate, and the organic carbon source comprises one or more of benzene, thiophene, pyridine, xylene and pyrimidine; and / or The first time is longer than 1 hour, and the second time is longer than 2 hours; and / or The addition amount of the organic carbon source relative to the metal salt is: 40 μL / g-100 μL / g, and the mass ratio of the zinc nitrate to the first product is 0.5-2:

100.

10. A secondary battery, characterized in that: include: A positive electrode sheet, wherein the positive electrode sheet is the positive electrode sheet according to any one of claims 6-7.

11. An electrical device, characterized in that: The secondary battery according to claim 10 is included.